1. EVALUATION OF VASCULAR CLOSURE DEVICES OUCOMES IN LARGE-BORE ENDOVASCULAR INTERVENTIONS (Vietnam Journal of Community Medicine, 2025)
Background: In endovascular interventions, achieving an adequately sized vascular access is crucial. However, vascular closure remains challenging, carrying a risk of complications. The use of ProGlide for closing small access sites has shown promising results. But, what are the outcomes of using ProGlide for large-bore access closure?Objectives: Evaluation of vascular closure device (ProGlide) outcomes in large - bore endovascular interventions.Method: A cross-sectional descriptive study of 36 cases of ProGlide use for vascular closure in large-bore endovascular interventions from 1/2023 to 1/2025 at Thong Nhat Hospital.Results: 36 cases, mean age 58.23; male 63.6%, female 36.4%. Target artery lesions requiring intervention: abdominopelvic artery 38.9%, abdominal aorta 50%. Femoral artery disease (TASC II A and B was 55.6%. Combined femoral access 36.1%. ProGlide 100% anterior closure type; operation time 3.4 minutes; hemostasis time 4.2 minutes; blood loss 10.3 ml; device success was 80.6%. Complications: intravascular thrombosis 22.3%; bleeding 16.7%; ProGlide suture rupture 5.6%. No deaths related to ProGlide device.Conclusion: Using ProGlide gives short hemostasis time, patients recover mobility early. Applying ProGlide device to close large access vessels gives positive results, can be applied.
Keywords: Vascular closure; large access; intervention.